2010
DOI: 10.1590/s0100-84042010000200017
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic properties of three Brazilian seaweeds

Abstract: -(Photosynthetic properties of three Brazilian seaweeds). Photosynthetic performance of distinct marine macroalgae, Ulva fasciata Delile (green alga), Lobophora variegata (J. V. Lamouroux) Womersley ex E. C. Oliveira (brown alga), and Plocamium brasiliensis (Greville) M. A. Howe & W. R. Taylor (red alga), were compared using a pulse amplitude-modulated fl uorometer. The maximum quantum yield (F v /F m ) ranged from 0.80 to 0.51, and the lowest value was found in P. brasiliensis. Under 400 μmol photons m -2 s -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, qP values did not demonstrate a significant reduction in the plants analyzed in the exposed understory. Given that qP reflects the proportion of the open state PSII reaction centers, the high values of qP can result either from high rates of electron transfer around PSII or from the occurrence of high non photochemical quenching processes (Chaloub et al, 2010) and thus maintain good photosystem health (Lage-Pinto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, qP values did not demonstrate a significant reduction in the plants analyzed in the exposed understory. Given that qP reflects the proportion of the open state PSII reaction centers, the high values of qP can result either from high rates of electron transfer around PSII or from the occurrence of high non photochemical quenching processes (Chaloub et al, 2010) and thus maintain good photosystem health (Lage-Pinto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The state of health of the seaweeds was assessed prior to the experiment using a diving Pulse Amplitude Modulator (PAM) Fluorometer (Zarges 40701 Heinz Walz GMBH) and after the 4 h incubation ( Chaloub et al, 2010 ; Leedham Elvidge et al, 2015 ; Li et al, 2014 ). The change in F v ∕ F m was calculated according to the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…Low values of F V /F M indicate that the algae are less tolerant to high radiation. Red algae usually have a lower F V /F M than that of green and brown macroalgae (Chaloub et al 2010), as observed for P. capillacea. Low ETR curves at 300 μmol(photon) m -2 s -1 could be expected for a shade-adapted alga, then the capacity for transfer and transport electrons through the electron transport chain of the photosystem is adapted for reducing the transport rate to avoid photoxidative excessive energy and oxidative stress (Bautista and Necchi 2008).…”
Section: Discussionmentioning
confidence: 67%